Isolated Lateral Rectus Myositis - A Case Series - S. Sheetal; R. S. Dhanya; S. Amith Kumar (Wolters Kluwer Medknow Publications, 2022)
Idiopathic orbital myositis is a rare, nongranulomatous, noninfective, nonneoplastic inflammation of the orbit. It can involve either a single extraocular muscle or multiple extraocular muscles, unilaterally or bilaterally. Isolated lateral rectus myositis is less commonly described. It can be diagnosed clinically or radiologically. The characteristic clinical features include painful eye movements, periorbital edema, proptosis, and diplopia. The typical features on magnetic resonance imaging include fusiform enlargement of the extraocular muscles, with enhancement on contrast. Treatment with corticosteroid results in prompt improvement in symptoms and remission. We hereby report two patients with isolated, acute, unilateral lateral rectus myositis.